2003
DOI: 10.1016/s0008-6363(03)00367-5
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles in cardiovascular diseases

Abstract: Microparticles are membrane vesicles released from many different cell types. There are two mechanisms that can result in their formation, cell activation and apoptosis. In these two mechanisms, different pathways are involved in microparticle generation. Microparticle generation seems to be a well regulated process. Microparticles vary in size, phospholipid and protein composition. They have a potent pro-inflammatory effect, promote coagulation and affect vascular function. Since these processes are all invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
439
0
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(455 citation statements)
references
References 85 publications
6
439
0
10
Order By: Relevance
“…Stimulus-induced shedding of plasma membrane-derived microvesicles-which bear distinctive complements of membrane markers-has been described in both hematopoietic cell types (platelets, DCs, and neutrophils) and non-hematopoietic cell types (epithelial cells, cancer cells, and neurons) [25][26][27][28][29]. The size of these released vesicles ranges between 100 nm and 1 μm in diameter which distinguishes them from the 1-4-μm apoptotic bodies containing fragmented DNA derived from damaged cells, and from the 30-80-nm exosomes (discussed below) derived from the intraluminal vesicles of endosomal multivesicular bodies (MVB).…”
Section: P2x7r Regulation Of Plasma Membrane Microvesicle Releasementioning
confidence: 99%
“…Stimulus-induced shedding of plasma membrane-derived microvesicles-which bear distinctive complements of membrane markers-has been described in both hematopoietic cell types (platelets, DCs, and neutrophils) and non-hematopoietic cell types (epithelial cells, cancer cells, and neurons) [25][26][27][28][29]. The size of these released vesicles ranges between 100 nm and 1 μm in diameter which distinguishes them from the 1-4-μm apoptotic bodies containing fragmented DNA derived from damaged cells, and from the 30-80-nm exosomes (discussed below) derived from the intraluminal vesicles of endosomal multivesicular bodies (MVB).…”
Section: P2x7r Regulation Of Plasma Membrane Microvesicle Releasementioning
confidence: 99%
“…Circulating microparticles are membrane vesicles mainly derived from platelets, but also from erythrocytes, leukocytes, and endothelial cells, 85 released after intensive cell activation, which enhance enzymatic reactions of the coagulation cascade by providing a large phospholipid surface, [86][87][88][89] and activating platelets, 90 thereby increasing the risk of thrombosis. Microparticles are, for example, associated with prothrombotic conditions such as heparin-induced thrombocytopenia, 86 TTP, 91 paroxysmal nocturnal hemoglobinuria, 92 and myocardial infarction.…”
Section: Microparticlesmentioning
confidence: 99%
“…Furthermore, it has been recently shown that cells may transiently modify the phenotype of neighboring cells by transferring surface receptors, intracellular proteins, and mRNA in mechanisms that involve exchange of cell-membrane-derived microvesicles (Ratajczak et al, 2006a,b). Shedding of membrane-derived microvesicles is a physiological phenom-enon that accompanies cell growth and cell activation, for example, hypoxia or oxidative injury (Beaudoin and Grondin, 1991;VanWijk et al, 2003;Morel et al, 2004;Hugel et al, 2005 -galactosidase).…”
Section: Bm-derived Stem Cells and Tissue/organ Regeneration: Evidencmentioning
confidence: 99%